Global corporate social responsibility initiatives for reluctant businesses - Khan, Syed Abdul Rehman, 1987- (Advances in business strategy and competitive advantage,, 2021)
"This book covers the emerging trends and best practices in the context of corporate social responsibility by providing the best practices, techniques, and empirical studies conducted around the globe from both developed and developing countries perspectives"--